“The Presentation of Grover’s Character in Thomas Wolfe’s The Lost Boy (مجلة ديالى للبحوث الانسانية, 2022)
Thomas Wolfe (1900-1938) is celebrated nowadays because of his untraditional way of writing that differentiates him from  his contemporaries’ to some extent. What are diagnosed to be his weaknesses at that time comes to be regarded as features of modernism now; his writings are shapeless in its form, he uses unique prose-poem style and rich languages, and his psychologically vivid characters that fluctuating in his philosophical time sequel concept.